Merunut Pola dan Perkembangan Sastra oleh Perempuan 1998 dan Periode Kekinian - Retno Endah Pratiwi (Puitika, 2023)
Rapid development occurred in the form of literary works born by emerging female writers pioneered by Ayu Utami as the initial foothold for the growth of other female writers. This research is intended to provide information related to the development of literature or literary works written by women since 1998 until now in the field of literature. The contributions that were also made by these women determined how the development of literature brought by these women as one of the successors of the existing literary process. In this study using descriptive analysis method. With the technique of observing and searching from various sources and works related to the elaboration of these women writers. There have been changes in writing styles in terms of fulfilling market tastes and pure writing patterns which are currently following the current developments of the times which do not only use similar writing patterns and characters, but new things are born from various other writers who have emerged.